Padrão de metilação da DMR do último éxon do gene IGF2 em ovócitos e células do cumulus de vacas nelore - Fagundes, Nadia Simarro (2009)
Assisted reproductive biotechnologies are essential instrument for the modern cattle breeding. In vitro embryo production (IVP) is prominence, situating Brazil as a country that more produce and transfer in vitro embryos in the word. In spite of the IVP big capacity to produce embryos per animal, this production can be better, being the oocyte quality the more important aspect of the system. The objective of this study was to evaluate the methylation pattern of the differentially methylated region (DMR) in the exon 10 of the IGF2 gene in oocytes and cumulus cells (CC) from immature and maturated nellore cows follicles.of 1 3 mm and ≥ 8.1 mm diameter. Cumulus-oocytes complexes (COCs) from ≥ 8.1 mm follicles had greater percentages of viable oocytes (40.5%) and nuclear maturation (60.6%). Immature oocytes from 1 3 mm follicles were less methylated (33.33% ± 34.79 %) than those immature from ≥ 8.1 mm follicles (83.69% ± 8.52%). After maturation, the methylation pattern were different among oocytes groups, ≥ 8.1 mm maturated follicles showed less methylation (18.51% ± 36.36%) than ≥ 8.1 mm immature follicles(83.69% ± 8.52%) and 1-3 mm maturated follicles (49.62% ± 34.00%). When evaluating only the oocytes by follicle size or maturation degree, these groups showed no significant differences between them. The CC showed no significant differences among treatments evaluated. The less methylated DMR pattern in the oocytes from ≥ 8.1 mm maturated follicles can be related with greater competency of those oocytes, however oocytes from 1 3 mm follicles can be with imprinting patters not completely established yet. It is concluded that DMR of the last exon of the IGF2 gene can be used as a molecular marker for epigenetic reprogramming status in oocytes, helping the IVP in the development and changes of new protocols.